Interactional Justice and Subjective Well-Being: A Contemporary Approach to Justice at Work Places - Sahai, Anjali; Mahapatra, Mamata (International Journal of Psychosocial Rehabilitation, 2020)
Organizations that include employees in the decision-making processes regarding their procedures increase their perceptions of justice. Interactional justice is the quality of interpersonal treatment people receive, and it has been reported that well-designed systems that promote interactional justice benefit both individuals and organizations. Subjective well-being (SWB), on the other hand, is the cognitive and affective evaluations related to people and their lives. For the purpose of the current study, interactional justice was measured through a scale developed by Moorman, Blakely & Niehoff (1998), and subjective well-being through a scale developed by Ed Diener (2004). The subscales of subjective well-being were the Satisfaction with Life Scale (SWLS), the Scale of Positive and Negative Experience (SPANE), and the Flourishing Scale (FS). Findings indicate a significant positive relationship between interactional justice and the subjective well-being of employees.